Effect of Rotation Speed on the Quality of Friction Welded AA 6061/AA 7075 Joints - Orhan, Ayhan; Asma, Yucel (Carl Hanser Verlag, 2014)
In this experimental study, the alloys AA6061 and AA7075 which have different properties but common usage areas such as aviation, space, and defence industry are difficult and problematic to be welded by conventional fusion welding methods. However, friction welding represents a modern and alternative joining method. For such welded joints, rotation speed was used as variable parameter, and so joints with different mechanical and microstructural properties were obtained. The crosssectional microstructure of friction welds were examined by optical microscopy. In order to determine the mechanical properties, microhardness and tensile tests were performed on the welded samples. Fracture surfaces obtained as a result of tensile tests were examined by scanning electron microscopy (SEM) and fracture type as well as fracture surface characteristics were investigated.
Keywords: Materials testing; friction welding; rotation speed; aluminium alloy